Projection of future pharmacy service fees using the dispensing claims in hospital and clinic outpatient pharmacies: national health insurance database between 2006 and 2012 - Dongmun Ha; Inmyung Song; Eui-Kyung Lee; Ju-Young Shin (BMC, 2018)
Abstract Background Predicting pharmacy service fees is crucial to sustain the health insurance budget and maintain pharmacy management. However, there is no evidence on how to predict pharmacy service fees at the population level. This study compares the status of pharmacy services and constructs regression model to project annual pharmacy service fees in Korea. Methods We conducted a time-series analysis by using sample data from the national health insurance database from 2006 and 2012. To reflect the latest trend, we categorized pharmacies into general hospital, special hospital, and clinic outpatient pharmacies based on the major source of service fees, using a 1% sample of the 2012 data. We estimated the daily number of prescriptions, pharmacy service fees, and drugs costs according to these three types of pharmacy services. To forecast pharmacy service fees, a regression model was constructed to estimate annual fees in the following year (2013). The dependent variable was pharmacy service fees and the independent variables were the number of prescriptions and service fees per pharmacy, ratio of patients (≥ 65 years), conversion factor, change of policy, and types of pharmacy services. Results Among the 21,283 pharmacies identified, 5.0% (1064), 4.6% (974), and 77.5% (16,340) were general hospital, special hospital, and clinic outpatient pharmacies, respectively, in 2012. General hospital pharmacies showed a higher daily number of prescriptions (111.9), higher pharmacy service fees ($25,546,342), and higher annual drugs costs ($215,728,000) per pharmacy than any other pharmacy (p <  0.05). The regression model to project found the ratio of patients aged 65 years and older and the conversion factor to be associated with an increase in pharmacy service fees. It also estimated the future rate of increase in pharmacy service fees to be between 3.1% and 7.8%. Conclusions General hospital outpatient pharmacies spent more on annual pharmacy service fees than any other type of pharmacy. The forecast of annual pharmacy service fees in Korea was similar to that of Australia, but not that of the United Kingdom.